2003
DOI: 10.1038/sj.leu.2403233
|View full text |Cite
|
Sign up to set email alerts
|

Role of curcumin and the inhibition of NF-κB in the onset of chemotherapy-induced mucosal barrier injury

Abstract: The inhibition of nuclear factor kappa B (NF-jB) by, for instance, curcumin is becoming an important new approach in combination with chemotherapy or irradiation for the treatment of a variety of cancers including haematological malignancies. A dose-limiting side effect of anticancer therapy in the gastrointestinal tract is mucosal barrier injury. It is hypothesised that mucosal barrier injury is initiated and amplified by proinflammatory-and NF-jB-regulated mediators. Therefore, the effect of NF-jB inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…1 It begins immediately after starting anticancer therapy with the activation of the nuclear transcription factor NF-kB resulting in the production and release of proinflammatory cytokines by various cells including lymphocytes, macrophages, endothelial cells and gut epithelial cells. 2,3 Gut epithelial cells produce not only proinflammatory cytokines like TNF-a, interleukin (IL)-1a and IL-6, but also the chemokines, monocyte chemoattractant protein-1 (MCP-1) and IL-8, antimicrobial peptides (defensins, cathelicidins, lactoferrin) and the acute phase protein, LPS-binding protein (LBP). [3][4][5] The release of proinflammatory cytokines and the blocking of clonogenic epithelial stem cell renewal results in apoptosis and necrosis, which manifests itself as epithelial atrophy and ulcerative lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 It begins immediately after starting anticancer therapy with the activation of the nuclear transcription factor NF-kB resulting in the production and release of proinflammatory cytokines by various cells including lymphocytes, macrophages, endothelial cells and gut epithelial cells. 2,3 Gut epithelial cells produce not only proinflammatory cytokines like TNF-a, interleukin (IL)-1a and IL-6, but also the chemokines, monocyte chemoattractant protein-1 (MCP-1) and IL-8, antimicrobial peptides (defensins, cathelicidins, lactoferrin) and the acute phase protein, LPS-binding protein (LBP). [3][4][5] The release of proinflammatory cytokines and the blocking of clonogenic epithelial stem cell renewal results in apoptosis and necrosis, which manifests itself as epithelial atrophy and ulcerative lesions.…”
mentioning
confidence: 99%
“…2,3 Gut epithelial cells produce not only proinflammatory cytokines like TNF-a, interleukin (IL)-1a and IL-6, but also the chemokines, monocyte chemoattractant protein-1 (MCP-1) and IL-8, antimicrobial peptides (defensins, cathelicidins, lactoferrin) and the acute phase protein, LPS-binding protein (LBP). [3][4][5] The release of proinflammatory cytokines and the blocking of clonogenic epithelial stem cell renewal results in apoptosis and necrosis, which manifests itself as epithelial atrophy and ulcerative lesions. 6 The latter are a potential portal of entry for oral viridans (alpha-haemolytic) streptococci (OVS), which are universal commensals of the oral cavity placing haematopoietic stem cell transplant (HSCT) recipients at risk of developing bacteraemia due to these bacteria.…”
mentioning
confidence: 99%
“…Two recent publications described the effect of curcumin on chemotherapy-and radiation-induced mucositis in animal models [24,25]. Both studies reported significant reduction in incidence and severity of mucositis in curcumin pre-treated animals.…”
Section: New Agents Of Potential Interestmentioning
confidence: 96%
“…11 Both reactive oxygen species and activation of the c-Jun NH2-terminal kinase pathway are crucial elements in the success of chemotherapy. 7 Curcumin may inhibit tumor growth via multiple mechanisms, including antitumor angiogenesis, 12,13 suppression of proliferation, 14,15 induction of apoptosis, 8,16 and prevention of metastasis. 17,18 However, the clinical applications of curcumin remain limited because of its short biological half-life, poor solubility resulting in poor absorption, and low bioavailability via the oral route.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence suggesting that curcumin is an ideal chemosensitizer for chemotherapy and that it helps to protect patients from the side effects of treatment. [5][6][7][8][9][10] Curcumin is a highly effective scavenger of reactive oxygen species and also inhibits the c-Jun NH2-terminal kinase pathway. 11 Both reactive oxygen species and activation of the c-Jun NH2-terminal kinase pathway are crucial elements in the success of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%